2020
DOI: 10.3934/jimo.2019008
|View full text |Cite
|
Sign up to set email alerts
|

Optimal production, pricing and government subsidy policies for a closed loop supply chain with uncertain returns

Abstract: This paper studies an original equipment manufacturer's (OEM's) optimal production and pricing decisions and the governments optimal subsidy level when the number of used products returning to the OEM is uncertain. The government aims to minimize its total expenditures but also attempt to achieve a given target collection level. We model the problem as an extended price-setting newsvendor model, which simultaneously incorporates supply uncertainty and external government influence. Moreover, we consider separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For the examination of the impact of government subsidies on private R&D, game theory and other theorybased models are used less often, but some studies do exist (e.g., [9,28,29]). e closest studies to the research of our paper are [24,30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the examination of the impact of government subsidies on private R&D, game theory and other theorybased models are used less often, but some studies do exist (e.g., [9,28,29]). e closest studies to the research of our paper are [24,30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…en, Chen et al studied the impact of the uncertain quantity of waste products and found that there is little essential difference between providing subsidies directly to manufacturers and consumers. Coordinating the supply chain requires government subsidies to achieve a higher target collection level [29]. Consider a manufacturer who sells a new product to consumers and examines the optimal recovery strategy and associated decisions by developing three models, further exploring the impacts of product quality and government subsidy on the optimal decisions [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recycling and reuse have become a hot topic in the textile and clothing industry. According to the report of circular fashion: China new textile economic outlook issued by China Textile Industry Federation, under the influence of "fast fashion", the global clothing utilization rate has decreased by 36% from 2000 to 2015, and more than 50% of fast fashion clothing will be discarded within one year [2]. Although the original textile production has made significant technological progress in environmental protection, low recovery rate and consumer awareness have an impact on the sustainability level of the textile industry [3].…”
mentioning
confidence: 99%
“…On the other hand, clothing reuse is a kind of consumer disposal behavior that has not been fully exploited, but it has an important impact on society. The survey shows that 75% of consumers think sustainability is extremely important; More than one-third of consumers are willing to choose brands with practices in environmental and social improvement, even if it may not be their preferred brand [2]. From the perspective of customer led logic, clothing reuse is a kind of consumer value creation behavior [9].…”
mentioning
confidence: 99%